Ultimate response and plastic design of aluminium alloy continuous beams. (May 2022) - Georgantzia, Evangelia; Gkantou, Michaela; Kamaris, George S.; Kansara, Kunal D.
Abstract: Over the last twenty years 6, 000 series aluminium alloys are gaining increasing attention as a structural material in the construction sector, particularly in applications where lightness and corrosion resistance are crucial for material selection. Aiming to sustainable construction practices, significant material savings could be achieved through more economical design solutions such as plastic design. Currently, plastic design of aluminium alloy structures is not permitted in most design codes, except European provisions which provide recommendations for inelastic analysis. Indeed, there is a clear lack of experimental data to prove this possibility, particularly for relatively new materials in the construction industry, such as the 6082-Τ6 heat-treated aluminium alloy. To address this knowledge gap, a total of 15 rectangular hollow sections fabricated from 6082-T6 aluminium alloy were tested as simply-supported and two-span continuous beams. Numerical models were developed to replicate the experimental results considering geometric and material nonlinearities. A subsequent parametric study was carried out to generate numerical data for indeterminate structures. One normal and two high strength aluminium alloys as well as two load configurations were examined within this parametric study over a wide range of cross-sectional aspect ratios and slendernesses. The experimental results in combination with the numerical results were utilised to assess the accuracy and applicability of (i) the traditional plastic design method, (ii) the European design provisions (EC9), (iii) the plastic hinge method included in Annex H of EC9, and (iv) the Continuous Strength Method (CSM). Relative comparisons demonstrated the potential of applying plastic design in aluminium alloy indeterminate structures. Notably, the plastic hinge method and the CSM which accounts for strain hardening at the cross-sectional level and for moment redistribution at the system level were found to provide the most accurate design strength predictions, resulting in more economical cross-sections and utilising the full potential of aluminium alloys' plastic deformability.